Environmental Vulnerabilities and Impact of EMS: Study of Indian Pharmaceutical Small and Medium Scale Industries - Bhasi A. Balakrishnan; Anjula Gurtoo (International Journal of Small and Medium Enterprises and Business Sustainability, 2016)
This paper evaluates the vulnerabilities faced by the small and medium scale enterprises (SMEs) in compliance to environmental regulations and explores the impact of environmental management systems on the firm’s compliance response. Based on a survey of 71 pharmaceutical firms from across India, two types of management systems are investigated, namely, ISO certification and establishment of a separate department. Analytical Hierarchy Process and test of significance analysis highlights that contrary to the conventional understanding that SMEs lack the wherewithal to comply with environmental standards, at least one third of the firms have taken pro-active steps to deal with compliance issues. External factors like unstable and non-aligned international standards create the main environmental management vulnerabilities. The firms with a formal environmental management system are seen to cope better, with more focus on meeting international standards and applying proactive strategies. Firms without a formal environmental management system continue to grapple with production issues. These and other results are discussed through the regulatory perspective.